Do capelo ao fardão: a inserção de professoras na academia sergipana de letras no século XX - Martires, José Genivaldo (2020)
This thesis investigates the insertion of professors in the Academy of Letters from Sergipe, Brazil, (ASL in Portuguese), during the 20th century, specifically from 1977 to 1998. This time frame is related to the entry of the first woman in ASL and the last one in the 20th century. During this period, six professor and teachers were elected: Núbia Marques (1977); Ofenísia Freire (1980), Maria Thétis Nunes (1982), Carmelita Pinto Fontes (1984), Giselda de Morais (1992), and Maria Lígia Madureira Pina (1997). ASL was created in 1929 by intellectuals who belonged to the Historical and Geographic Institute of Sergipe (IHGSE in Portuguese) and the association "A hora literária" (literary time in English), which adopted Brazilian Academy of Letters (ABL in Portuguese) model. The election of women was admitted only in 1977. I used the following categories: field, capitals (Bourdieu, 1996, 2002); intellectuals, and sociability network (Sirinelli, 2003). I also used oral sources, written and visual documentation, and references on topics related to the issues addressed in this thesis. I carried out documentary research on ASL archive; ABL archive; Epifânio Doria Public Library (BPED in Portuguese), State Council of Culture of Sergipe (CEC in Portuguese) archive; State Education Council of Sergipe (CEE in Portuguese) archive; Sergipe State Public Archive (APES in Portuguese); IHGSE newspaper archive; Brazilian Historical and Geographic Institute (IHGB in Portuguese) archive; Municipality of Aracaju (PMA in Portuguese) archive, and Federal University of Sergipe (UFS in Portuguese). The academic professors and teachers who entered the ASL in the 20th century completed secondary education at the Rui Barbosa Education Institute were Ofenísia Freire, Lígia Pina, and Carmelita Fontes; at Atheneu Sergipense School Thétis Nunes, Núbia Marques, and Gizelda Morais. They continued their studies in higher education obtaining degrees in several areas. Of these, only Ofenísia Freire did not continue pedagogical training in higher education. After this stage of formation, they started their teaching trajectories. All of them taught in secondary school, starting in the 1940s. Except for Ofenísia Freire and Lígia Pina, the others were professors in higher education, mainly at UFS. Through the exercise of teaching, they also established networks of sociability in educational and cultural spaces such as IERB, Atheneu Sergipense, Catholic Faculty of Philosophy of Sergipe, at IHGSE, at Sergipe State Council of Culture, and the Federal University of Sergipe. In the latter place, all of them exercised activities for more time. Their trajectories in these spaces contributed to the expansion of the cultural capital necessary for joining ASL. Within the scope of ASL, these professors/teachers published in the main media for the dissemination of the sodalitium, that is, the Revista da Academia Sergipana de Letras and the Jornal Letras Sergipanas. The speeches, publications in the ASL magazine and newspaper served as a showcase for the recognition of these professors/teachers concerning their peers and contributed to the accumulation of cultural capital. Their trajectory, their literary paths, and their meetings show how the exercise of teaching contributed to their insertion in sociability networks and capital accumulation that guaranteed to these professors' legitimation and insertion in the androcentric space of ASL.